Reality gendervision : sexuality & gender on transatlantic reality television - Weber, Brenda R., 1964- (Duke University Press, 2014)
This essay collection focuses on the gendered dimensions of reality television in both the United States and Great Britain. Through close readings of a wide range of reality programming, from Finding Sarah and Sister Wives to Ghost Adventures and Deadliest Warrior, the contributors think through questions of femininity and masculinity, as they relate to the intersections of gender, race, class, and sexuality. They connect the genre's combination of real people and surreal experiences, of authenticity and artifice, to the production of identity and norms of citizenship, the commodification of selfhood, and the naturalization of regimes of power. Whether assessing the Kardashian family brand, portrayals of hoarders, or big-family programs such as 19 Kids and Counting, the contributors analyze reality television as a relevant site for the production and performance of gender. In the process, they illuminate the larger neoliberal and postfeminist contexts in which reality TV is produced, promoted, watched, and experienced.